Oxidized Low-Density Lipoproteins increases nivolumab-induced cardiotoxicity through TLR4/NF-KB and NLRP3 pathways. (14th October 2021) - Quagliariello, V; Bonelli, A; Paccone, A; Buccolo, S; Iovine, M; Botti, G; Maurea, N
Abstract: Background: Atherosclerosis is now recognized as a chronic inflammatory disease. Oxidized low-density lipoprotein (Ox-LDL) is oxidatively modified form of LDL with a key role in induction and progressio of atherosclerosis. Recent findings reported that cardiovascular events (myocarditis and atherosclerosis) were higher after initiation of immune check-point inhibitors (ICIs), potentially mediated by accelerated progression of atherosclerosis. Purpose: We evaluated whether ox-LDL-induced apoptosis through toll-like receptor-4 (TLR4)/Nuclear factor κB (NF-κB) signaling pathway and NLRP3 inflammasome during exposure of human cardiomyocytes to nivolumab turning the light on the mechanisms of cell inflammation induced by OxLDL in cardiotoxicity of ICIs. Methods: Human fetal cardiomyocytes (HFC cell line) in co-culture with hPBMC, were exposed to clinically relevant concentration of nivolumab (100 nM) alone or combined to OxLDL at 1, 10 and 50 μg/mL for 24h. After the incubation period, we performed the following tests: determination of cell viability, through analysis of mitochondrial dehydrogenase activity, study of lipid peroxidation (quantifying cellular Malondialdehyde and 4-hydroxynonenal), intracellular Ca2+ homeostasis and apoptosis. Moreover, pro-inflammatory studied were also performed (activation of NLRP3 inflammasome, expression of TLR4 and NF-kB). In order to evaluate the pathways involved in OxLDL damages, TLR4 and NLRP3 inhibitor (TAK-242 and dapansutrile, respectively) were added during cell viability and apoptosis studies. Results: Nivolumab exerts cytotoxic and pro-apoptotic effects in co-coltures of cardiomyocytes and hPBMC. OxLDL increases significantly the nivolumab-induced cardiotoxicity in a manner that is sensitive to TLR4 and NLRP3. Incubation of cardiomyocytes with ox-LDL (10 and 50 μg/mL) for 24 hours increased TLR4 and NF-κB expressions. Ox-LDL had pro-apoptotic effects in a concentration-dependent manner with the involvement of lipid peroxidation but not of intracellular calcium. Conclusion: Ox-LDL exacerbates cardiotoxicity during exposure to nivolumab through pro-inflammatory mechanisms. These results place the first step to preclinical studies aimed to reduce ox-LDL during treatment with ICIs through pharmacological inhibition or by changing diet and lifestyle. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministero della Salute, Ricerca Corrente project